Effect of rutin on pharmacokinetic modulation of diclofenac in rats. (1st November 2020) - Dogra, Ashish; Gour, Abhishek; Bhatt, Shipra; Sharma, Priyanka; Sharma, Anjna; Kotwal, Pankul; Wazir, Priya; Mishra, Prashant; Singh, Gurdarshan; Nandi, Utpal
Abstract: Diclofenac is an extensively used nonsteroidal anti-inflammatory drug, but gastrointestinal liabilities and cardiovascular complications take the shine away from such a widely prescribed drug. On the other hand, rutin, a dietary bioflavonoid, has quite a few pharmacological attributes to improve the efficacy and reduce the dose-related toxicities of diclofenac through the intended food-drug/herb-drug interaction. The aim of the present research work was to investigate the role of rutin on pharmacokinetic modulation and the consequent efficacy of diclofenac. At first, pharmacodynamics and pharmacokinetics of diclofenac as alone and in the presence of rutin were investigated orally in a rat model. Then, mechanistic studies were performed to explain the effect of rutin on improvement in oral exposure as well as the efficacy of diclofenac using a battery of in-vitro / in-situ / in-vivo studies. Results displayed that rutin enhanced efficacy as well as oral bioavailability of diclofenac in rats. A marked increase in permeability of diclofenac by rutin was displayed that is linked to inhibition of Breast Cancer Resistance Protein (BCRP) transporters. There was no significant effect of rutin on the modulation of intestinal transit, CYP2C9 inhibition in human liver microsomes, and CYP2C9/CYP2C11 expression in rat liver tissues to boost the oral exposure of diclofenac. Rutin is found to be an inhibitor for BCRP transporters and can act as an oral bioavailability enhancer for a drug like diclofenac.